Multivesicled forms and migration of hepatic hidatid cysts. - Perdomo, Roberto; Ferreira, Ciro; Chiesa, Antonio; Alvarez, Carmelo (Cirugía del Uruguay, 1988)
Based on everyday observations of composition and evolutionary behaviour of hepatic hydatid cysts, and supported by nationai and forelgn authors' valuable oplnlons, the following conclusions are reached: 1. The multivesicled hydatlde cysts are usually forms of local secondary echinococcosis and constitute real intra-adventicial secondary hydatid collections (IASHC), where the mother membrana of the primitiva cyst Is almost always torn and more or less disin• tegrated. 2. The Dévé scheme concernig multivesicled primitiva cyst', where primitiva (intact mother membrana) and secondary (second and third generation vesicles) echinococcosis coexist is difficult to find in practice. At best, it would constitute a brial and transitory torm of evolution towards more frequent ones. 3. The behaviour of IASHC is unique, and their evolutionary tendency is towards diverticularization, with the formation of secondary chambers that stimulate exogenous vesiculation, particularly towards the thorax through one or more irregular transdiaphragmatic routes and/or orificas.